The Effect of a Computerized Growth-Mindset Intervention on Teaching Students’ Mindset and Cognitive Stress Appraisal - Montagna, Melissa Joy; Marksteiner, Tamara; Dickhäuser, Oliver (Frontiers in Education, 2021)
The present study assessed the impact of a one-time computerized mindset intervention on teaching students’ cognitive stress appraisal before an upcoming exam. Previous research highlights the long-term effectiveness of growth-mindset interventions. Based on theoretical assumptions derived from the transactional stress theory as well as recent empirical evidence on intelligence mindset and stress, we proposed that changing students’ mindset would also impact their cognitive stress appraisal. In order to test this hypothesis, a sample of teaching students received a one-time computerized growth-mindset intervention aiming to foster viewing abilities as incremental. We found a significant as well as relatively lasting impact on participants’ mindset but no significant effect on participants’ stress appraisal. Nevertheless, an exploratory mediation analysis revealed that the intervention’s effect on participants’ appraisal of their coping ability (as part of the cognitive stress appraisal) was fully mediated by participants’ mindset. The results highlight the effectiveness of the utilized intervention and provide first practical insights into how a person’s mindset and their stress appraisal relate.